Virtual and Augmented Reality as Tools for Enhanced Science Instruction - Salman Hidayat; Herri Setiawan; Lili Herawati; Kittisak Rattanapong (Gema Cendekia Institute, 2026)
This study investigates the role of Virtual Reality and Augmented Reality as tools for enhanced science instruction. It addresses persistent challenges in science education, including low student engagement, difficulty in understanding abstract concepts, and limited access to laboratory experiences. Using a structured experimental design, the research examines how immersive technologies influence learning outcomes, motivation, and classroom engagement. The findings show that both Virtual Reality and Augmented Reality improve students’ conceptual understanding and learning performance. Virtual Reality has strong effects on spatial reasoning and deep conceptual focus through fully immersive environments. Augmented Reality supports contextual learning by linking digital representations with real-world laboratory settings. Students exposed to immersive instruction demonstrate higher attention, curiosity, and active participation compared to those in traditional settings. Motivation emerges as a key factor mediating learning gains. Immersive activities encourage exploration, inquiry, and sustained engagement, which support deeper cognitive processing. The study also finds that effectiveness depends on pedagogical alignment. Learning gains are strongest when technologies are integrated with clear objectives, guided inquiry, and reflective discussion. The results suggest that immersive technologies complement conventional instruction and expand opportunities for meaningful and effective science learning experiences.